Influence of Liquidity, Dividend Policy and Profitability on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2021 - Suryadi, Dodi; Mulyadi, Olandari (Jurnal Informatika Ekonomi Bisnis, 2023)
This study aims to determine the effect of liquidity, dividend policy and profitability on company value in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The population used in this study was Manufacturing Companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period while the sample of this study was 65 companies in manufacturing companies listed on the Indonesia Stock Exchange. The sample selection technique in this study used purposive sampling technique with the aim of obtaining a representative sample according to predetermined criteria. The amount of data used by each company is as much as 5 years multiplied by 65 companies, so that 325 financial statements of manufacturing companies are obtained. The type of data used is secondary data obtained from www.idx.co.id. The analysis method used is multiple linear regression analysis using IBM SPSS Statistics software version 25. This study obtained the result that Likuditias partially had a positive and significant effect on the value of the company with a significant value of 0.005. The dividend policy partially has a positive and significant effect on the value of the company with a significant value of 0.257. Profitability partially has a positive and significant effect on the value of the company with a significant value of 0.000. Liquidity, dividend policy and profitability together have a positive and significant effect on the value of the company with a significant value of 0.000. The results of the R2 test (coefficient of determination) on the adjusted r-square showed that the percentage of contribution of independent variables to the dependent variables was 0.226 or 22.6%.